You can count on me [videorecording (Blu-Ray)] - Linney, Laura; Ruffalo, Mark; Culkin, Rory; Broderick, Matthew, 1962-; Lonergan, Kenneth; Lonergan, Kenneth (Criterion collection, 2025)
Celebrated playwright Kenneth Lonergan first brought his rich, humanist vision to the screen with this soulful look at the complexities of a sibling relationship whose roots are as knotted as they are deep. Years after Sammy and her younger brother, Terry, lost their parents in a car crash, small-town single mother Sammy is plunged into another crisis when the troubled, adrift Terry comes home for what turns out to be an extended stay one that could either bring them closer together or tear them apart. With infinite grace and his peerless ear for dialogue, Lonergan offers something all too rare on-screen: beautifully flawed human beings whose journeys offer achingly relatable insight into what changes when you grow up and what doesn't.